Measurement and prevalence of circulating ADAMTS13‐specific immune complexes in autoimmune thrombotic thrombocytopenic purpura. (March 2014) - Lotta, L. A.; Valsecchi, C.; Pontiggia, S.; Mancini, I.; Cannavò, A.; Artoni, A.; Mikovic, D.; Meloni, G.; Peyvandi, F.
Summary Background The formation of ADAMTS13‐specific circulating immune complexes (CICs) may be a pathophysiologic mechanism in autoimmune thrombotic thrombocytopenic purpura (TTP), but has not been systematically investigated. Objectives (a) To develop an assay for ADAMTS13‐specific CICs; (b) to evaluate their prevalence in autoimmune TTP; and (c) to assess their association with ADAMTS13‐related measurements and clinical features in autoimmune TTP patients. Patients/Methods We developed and validated an ELISA method for ADAMTS13‐specific CICs. ADAMTS13‐specific CICs were searched for in 55 patients with autoimmune TTP from the Milan TTP Registry (URL:http://www.ttpdatabase.org/) and 28 controls. The associations between ADAMTS13‐specific CIC levels and ADAMTS13 activity, antigen, anti‐ADAMTS13 IgGs and acute TTP clinical features were assessed by multivariate linear regression. Results Intra‐ and inter‐assay coefficients of variation of the new test were 5.3 and 9.6%. In 36 patients with severe ADAMTS13 deficiency and anti‐ADAMTS13 autoantibodies, the prevalence of ADAMTS13‐specific CICs was 47% (n = 17; 95% confidence interval [CI], 32–63%). ADAMTS13‐specific CICs were detected also in seven of 19 (37%; 95% CI, 19–59%) patients with reduced ADAMTS13 activity, but apparently negative anti‐ADAMTS13 autoantibodies. ADAMTS13‐specific CICs were not associated with ADAMTS13 activity, antigen or anti‐ADAMTS13 IgGs. In patients with acute TTP, increasing levels of ADAMTS13‐specific CICs were associated with a higher number of plasma‐exchange procedures required to attain remission (per 0.1 increase in normalized OD values, beta, 2.9; 95% CI, −0.7 to 6.5). Conclusions Approximately one to two‐thirds of patients with autoimmune TTP display ADAMTS13‐specific CICs. A thorough investigation of the prognostic relevance of ADAMTS13‐specific CIC levels in autoimmune TTP is warranted.